The effect of distance to elite sport teams on talent development in German handball players - Farah, L.; Wattie, N.; Baker, J.; Büsch, D.; Schorer, J. (2019 SCAPPS Conference. Vancouver, BC, Canada, October 17 -19, 2019, 2019)
The proximity of youth athletes to elite sport teams has been shown to have positive developmental effects in Canadian, Irish and Danish athletes (Farah et al., 2018; Finnegan et al., 2016; Rossing et al., 2018). However, this effect has not been explored in Germany; a country that is much different in its geospatial and sport-systematic nature. The purpose of this study was twofold: a-to explore the influence of distance from birthplace and first club to elite sport teams on selection into the youth national handball team, and b-to examine the long-term effects of distance on the league-level reached years later. Birthplace and first club data were collected for 60 female and 36 male athlete selected into the national youth program, as well as 59 female and 34 male athletes whom were not. Results showed that selected male athletes were closer to elite teams than their non-selected counterparts; however, only distance from birthplace to sex-specific second-division teams reached significance (p = .04, d = .52). As for female athletes, there were no differences in distance between the two groups. In regards to our second objective, distances from birthplace and first clubs to first-division teams significantly varied across league levels but in no particular pattern (p<0.01 and p = 0.02, respectively), while no differences were observed in the female group. These findings suggest that distance to elite teams have a positive influence on the development of male German handball players, yet has no effect on female athletes in this population